Google hacking for penetration testers - Long, Johnny; Gardner, Bill; Brown, Justin (Syngress, 2016)
Google's search capabilities are so powerful, they sometimes discover content that no one ever intended to be publicly available on the Web, including social security numbers, credit card numbers, trade secrets, and federally classified documents. This book shows how security professionals and system administrators manipulate Google to find sensitive information in order to "self-police" their own organizations.
Includes index. - Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed December 14, 2015)
Keywords: Google; Web search engines; Computer security; Internet programming; Internet -- Security measures; Computer networks -- Security measures; Moteurs de recherche sur Internet; Sécurité informatique; Programmation Internet; Internet; Sécurité; Mesures; Réseaux d'ordinateurs; Sécurité; Mesures; Computer networks; Security measures; Internet; Security measures